1998
DOI: 10.1097/00042560-199804010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Virologic, Immunologic, and Clinical Parameters in the Incidence and Progression of Anal Squamous Intraepithelial Lesions in HIV-Positive and HIV-Negative Homosexual Men

Abstract: Anal cancer may be preceded by anal squamous intraepithelial lesions (ASIL), but the natural history of ASIL is poorly understood. In this report, we characterize the 2-year incidence and progression of low-grade SIL (LSIL) and high-grade SIL (HSIL) in a cohort study in 346 HIV-positive and 262 HIV-negative homosexual or bisexual men. Subjects were studied at defined intervals using anal cytology, anoscopy with biopsy of visible lesions, human papillomavirus (HPV) testing, HIV serostatus, CD4 level, and data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
160
0
12

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(182 citation statements)
references
References 13 publications
10
160
0
12
Order By: Relevance
“…Several studies have reported a two to six times greater prevalence of HPV infection in immunosuppressed patients [23][24][25][26][27][28] and twice the risk of progression from low-grade AIN to high-grade AIN. [27][28][29][30] AIN lesions are known to advance from low-grade to high-grade AIN within 2 years of diagnosis in 36-66% of individuals with progression occurring more rapidly and more frequently in immunodeficient individuals. 27,30 Our study confirms the increasing prevalence of high-risk HPV with worsening dysplasia: 56% of AIN I, 80% of AIN II, and 88% of AIN III, findings earlier reported by Varnai et al 31 32 In our study, six (60%) of AIN II lesions were non-16 high-risk HPV types; five of which on follow-up showed less severe lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported a two to six times greater prevalence of HPV infection in immunosuppressed patients [23][24][25][26][27][28] and twice the risk of progression from low-grade AIN to high-grade AIN. [27][28][29][30] AIN lesions are known to advance from low-grade to high-grade AIN within 2 years of diagnosis in 36-66% of individuals with progression occurring more rapidly and more frequently in immunodeficient individuals. 27,30 Our study confirms the increasing prevalence of high-risk HPV with worsening dysplasia: 56% of AIN I, 80% of AIN II, and 88% of AIN III, findings earlier reported by Varnai et al 31 32 In our study, six (60%) of AIN II lesions were non-16 high-risk HPV types; five of which on follow-up showed less severe lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] AIN lesions are known to advance from low-grade to high-grade AIN within 2 years of diagnosis in 36-66% of individuals with progression occurring more rapidly and more frequently in immunodeficient individuals. 27,30 Our study confirms the increasing prevalence of high-risk HPV with worsening dysplasia: 56% of AIN I, 80% of AIN II, and 88% of AIN III, findings earlier reported by Varnai et al 31 32 In our study, six (60%) of AIN II lesions were non-16 high-risk HPV types; five of which on follow-up showed less severe lesions. One AIN II with HPV 16 had followup and progressed to AIN III.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely a result of the fact that HIVpositive patients are more likely to be infected with HPV, often with more than one subtype [15]. Additionally, HIV patients are more likely to have HPV-associated squamous intraepithelial lesions (SILs), particularly those considered high grade [15][16][17]. Development of these HSILs appears to be inversely related to CD4 count [16 -18].…”
Section: Hivmentioning
confidence: 99%
“…The role of viral load, medication status, and CD4 count was not assessed, and there is one limitation in this study. Studies have also demonstrated that HIV-positive patients with AIN I were more likely to progress to higher grade lesions, while HIV-negative patients were more likely to have no disease at two-year follow-up [16]. Despite these findings, AIN II/III is less likely to regress regardless of HIV status [17].…”
Section: Discussionmentioning
confidence: 99%